Modeling of piezoelectric stack actuators considering bonding layers. (November 2015) - Zhu, Wei; Chen, Gangli; Rui, Xiaoting
In order to achieve large displacement output of piezoelectric actuators, piezoelectric stack actuators are realized by mechanically layering or stacking multi-chip piezoelectric wafers in series and electronically connecting electrodes in parallel. Experimental investigations show that different layering or stacking processes greatly affect the dynamic performances of piezoelectric stack actuators. We consider that a linear force and a hysteretic force will be generated by all piezoelectric wafers under the applied voltage to a piezoelectric stack actuator, and the total force will result in the forced vibration of the system consisted of multi-chip piezoelectric wafers and bonding layers. Based on the above-mentioned opinion, an electromechanical model is put forward using a Bouc–Wen hysteresis operator to model the hysteretic force and the transfer matrix method for multibody system to establish the dynamic equation of the piezoelectric stack actuator. This research shows that (1) the layering or stacking processes do not affect the hysteretic characteristics of piezoelectric stack actuators and (2) the layering or stacking processes change the dynamic performance of piezoelectric stack actuators by changing the parameters of the bonding layers. These two conclusions are consistent with the experimental results.